Intensification Of Civil Servant Work Discipline In The Public Works And Spatial Planning Service (PUPR) - Ricky Muliawan Hansyar; Al Asri Abubakar; Halimah Halimah (STABN RADEN WIJAYA WONOGIRI, 2025)
The Public Works and Housing Agency of Pidie Regency is one of the agencies in Pidie Regency, one of its tasks is to guide Civil Servants to be more obedient and compliant with the disciplinary regulations that have been stipulated in the applicable laws and regulations so that the implementation of duties can be carried out in accordance with existing provisions. Civil Servant Development includes several things including the preparation and determination of needs, procurement, rank and position, and others. However, all of these aspects have not been implemented optimally because various constraints or inhibiting factors have been encountered. The purpose of the study was to determine the extent to which the intensification of Civil Servant discipline has been implemented at the Public Works and Housing Agency of Pidie Regency and what obstacles have been encountered. This study uses a descriptive method. To obtain data, it is necessary to conduct field and library research. All data obtained are processed and analyzed using a qualitative approach method. The results of the study indicate that the intensification of Civil Servant discipline at the Public Works and Housing Agency of Pidie Regency has not been implemented as it should because various inhibiting factors have been encountered. The obstacles encountered include, among others, the limited ability of employees to carry out the tasks assigned to them, and the lack of guidance provided by superiors to their subordinates.